Unravelling the unseen ‘C’ with the cone beam computed tomography: a rare case report - Suneja, Ekta Singh; Baweja, Parvinder Singh; Behl, Ashima Bali; Bhagat, Saurabh; Bajaj, Kavisha; Mahajan, Surbhi (International Journal of Research in Medical Sciences, 2022)
Recognition of aberrant root canal configurations is critical to successfully negotiate and treat a canal and one of such aberrancies is a C shape root canal system. The fins and webs present in a C shape canal system presents a challenge to debridement and obturation. Knowledge of variations through advanced imaging modalities like CBCT, rotary and hand instruments assisted with ultrasonics and modified obturation techniques aid in effective management of C shaped root canals. This case report presents a successful endodontic management of a rare c shape canal configuration in a mandibular second premolar with the aid of the cone‑beam computed tomography (CBCT) scanning imaging technique.